Correlation in telomere lengths between feathers and blood cells in pied flycatchers. (16th April 2020) - Kärkkäinen, Tiia; Bize, P.; Stier, Antoine
Abstract : The length of telomeres (i.e. the protective non‐coding DNA repeat sequences capping the end of eukaryotic chromosomes) is drawing an increasing attention in ecology and evolution as a biomarker of individual state and fate. Bird erythrocytes are nucleated and telomere measurements using blood derived DNA has become the gold standard in avian biology. However, blood sampling is not trivial and not achievable under all field conditions. We investigated whether feather DNA could be used as an alternative or complementary approach to blood DNA when assessing telomere length with the quantitative PCR method. Indeed, investigating telomere length in different tissues may provide more detailed information regarding both the determinants and the importance of telomere length for avian life histories. We collected tertiary feathers on the same day as a blood sample in adult and 12‐day‐old nestling pied flycatchers Ficedula hypoleuca . Our results show a positive but moderate relationship between telomere length measured using DNA derived from blood and feather samples. This relationship was stronger in nestlings than in adults. Nestlings had longer telomeres in blood than in feathers while no significant difference was observed in adults. Hence, our study demonstrates that feathers can provide a complementary approach to blood for telomere measurements in wild birds, and we discuss further methodological considerations when using feathers for telomere measures. Telomeres seem to show faster erosion with age in blood than feathers, which may account for the lower correlation in telomere lengths between the two tissues in adults.